Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1080/00207450601042094
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Cognitive Performance and Mood by Aromas of Peppermint and Ylang-Ylang

Abstract: This study provides further evidence for the impact of the aromas of plant essential oils on aspects of cognition and mood in healthy participants. One hundred and forty four volunteers were randomly assigned to conditions of Ylang-Ylang aroma, Peppermint aroma, or no aroma control. Cognitive performance was assessed using the Cognitive Drug Research computerised assessment battery, with mood scales completed before and after cognitive testing. The analysis of the data revealed significant differences between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
118
2
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 147 publications
(136 citation statements)
references
References 31 publications
5
118
2
4
Order By: Relevance
“…Mood assessments were also significantly affected, with rosemary producing increased alertness and contentedness. Further to this, Moss and colleagues found that peppermint aroma resulted in significantly improved quality of memory when compared to ylang-ylang aroma and a no aroma control group [14]. These findings were found not to be associated with changes in mood measurements.…”
mentioning
confidence: 68%
“…Mood assessments were also significantly affected, with rosemary producing increased alertness and contentedness. Further to this, Moss and colleagues found that peppermint aroma resulted in significantly improved quality of memory when compared to ylang-ylang aroma and a no aroma control group [14]. These findings were found not to be associated with changes in mood measurements.…”
mentioning
confidence: 68%
“…Warm and colleagues [6] demonstrated that Peppermint (Mentha piperita) aroma could enhance vigilance performance independent of subjective evaluations of stress during task performance. In contrast Peppermint aroma has been demonstrated to positively impact on both cognition and changes in pre-to post-testing mood state when compared to Ylang Ylang [7]. Clearly, the type of cognitive assessments, subjective variables and the timing of their recording play important roles in the pattern of effects observed.…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, we aim to explore how the cognitive performance of the students is impacted by an incongruent olfactory design. This is motivated by interesting results that showed how memory was enhanced in the presence of the peppermint smell [41] as well as by our previous work [22]. Another interesting approach in designing the olfactory feedback would be to take into account crossmodal associations existent between modalities (e.g., deliver a citric smell corresponding to the hexagonal design of the map) [51].…”
Section: Affordances and Limitationsmentioning
confidence: 99%